Evaluation of an Ultra-Short MRI Protocol for Cerebral Staging Examinations in Melanoma Patients - Peters, Sönke; Gärtner, Friederike; Austein, Friederike; Wodarg, Fritz; Jansen, Olav; Hensler, Johannes (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Due to its high sensitivity and lack of radiation, MRI is often used to stage cerebral tumors in patients. In contrast, the relatively long examination times and the limited availability of MRI slots at the clinic might delay these examinations. The aim of this study was to compare an ultra-short MRI protocol with the routinely used standard protocol.Materials and Methods Cerebral MRI of 147 patients with malignant melanoma were evaluated retrospectively, whereby only two sequences (FLAIR images and contrast-enhanced T1 MPR images) were evaluated in one group and images from the whole examination were available for the second group, including five sequences (DWI, T2 TSE, FLAIR, native and contrast-enhanced T1 TSE, and contrast-enhanced T1 MPR). The results of the two groups were compared and tested to determine whether the ultra-short approach was inferior to the full examination.Results 13.6 % of the patients had cerebral metastases. Overall, 73 metastases were detected: 60 were located supratentorially and 13 infratentorially. Concerning the detection of cerebral metastases, the ultra-short MRI examination, involving only a FLAIR and a contrast-enhanced T1 MPR sequence, was not inferior to the full MRI protocol in general (p = 0.017) and separated by location for supratentorial (p = 0.026) and infratentorial (p = 0.001) metastases.Conclusion For staging purposes, a focused, ultra-short MRI protocol is not inferior to a standard MRI examination. This might open up opportunities for faster staging processes and a more efficient use of the often-restricted MRI capacities.Key Points Citation Format
Keywords: MR imaging; melanoma; metastases; CNS; brain neoplasms; brain; radiologists; staging